Multiloop Edgewise Arch-wire Technique for Skeletal Class III Openbite: A Case Report - Basukala, Dharma Laxmi (Orthodontic Journal of Nepal, 2017)
Skeletal Class III with openbite is one of the most difficult malocclusion to treat orthodontically. Generally, the morphological characteristics of this malocclusion are poor antero-posterior growth of the maxilla or excessive growth of the mandible with high angle. An 18-year-old male had Class III malocclusion with retrognathic maxilla and normal mandible with high angle. All third molars except on fourth quadrant were extracted to eliminate the posterior crowding. Multiloop Edgewise Arch-wire (MEAW) technique was used to upright the mesially inclined buccal teeth and to correct occlusal plane. In nine month time, anterior cross bite and open bite were corrected; normal overjet, overbite and Class I canine relation were achieved.